The Implementation of Canva Through Poster Creation on Fourth Graders - Mahendro, Rasika Tasdyatta; Hadiyansyah, Dhuha; Herwandar, Ria; Herwandar, Era; Adrimurlan, Raditya Daffa; Iskandar, Farhan Alfarizi (UniversitasAl Azhar Indonesia, 2023)
This community service program introduced Canva, a graphic design platform, to elementary school students as part of the University of Al-Azhar Indonesia’s Gerakan Nasional Revolusi Mental, under the theme of “Digital Literacy and Ethics”. The program was carried out at Al-Fityan School Tangerang on August 21, 2023. Students, in 4th grade, were trained to create a poster using Canva. They were asked to choose one of their five favorite things: mom, dad, hobby, food, or animal. The results showed that the popular choice was between “hobby” and “animal” while the least popular was “dad”. All 28 students produced their own posters and even six of them produced two posters. In this regard, the training of Canva seemed to be effective. There should be a continuation of training using the similar theme to Al-Fityan students for the future program given students’ progress and enthusiasm.Keywords – Canva, Gerakan Nasional Revolusi Mental, Poster Creation, Fourth Graders, Digital Literacy